REAL TIME CHROMAMETRY MEASUREMENT FOR FOOD QUALITY DETECTION USING MOBILE DEVICE - MOHAMAD HUSSIN, NUR HAZIQAH FARAH (Universiti Teknologi PETRONAS, 2017)
Quality food is essential in current lifestyle to ensure a good living. For the past years, many research have been performed into checking the quality of food such as; by using smart packaging, sensor stickers, time-temperature control of food freshness. One common thing from the current technologies is most of the method used a colour changing labels to indicate the changes of food quality. The indicator will only shows colour instead of stating the freshness of the food. Limitations exist in the current technologies due inaccuracy reading of the colour of labels. As stated from Colour Blindness Awareness, 1 in 12 men and in 200 women have colour blindness. Hence, reading the colours using humans eyes have weaknesses for some users.